Dampak COVID-19 terhadap Pendapatan Pedagang di Pasar Transit Passo - Wakim, Chirsmona; Papilaya, Josep; Rehatta, Geradin (Jurnal Pendidikan Ekonomi, 2022)
The Covid-19 pandemic has significantly impacted the micro-enterprise sector, including traditional market traders. This study aims to analyze changes in the income of staple goods traders at the Transit Market in Passo before and after the pandemic. A quantitative approach with an ex post facto design was employed. The sample consisted of 15 permanent traders selected purposively. Data were collected through questionnaires and analyzed using linearity tests (ANOVA) and the Paired Sample t-Test. The results show that the average daily income of traders decreased from IDR 7,000,000 to IDR 3,700,000. The ANOVA test indicated a significant linear relationship between pre- and post-pandemic income (Sig. = 0.001), with no deviation from linearity (Sig. = 0.637). The Paired Sample t-Test confirmed a statistically significant difference (t = 10.104; Sig. = 0.000). In conclusion, the Covid-19 pandemic had a real impact in reducing the income of traders at the Transit Market in Passo. These findings highlight the need for targeted local economic recovery policies, including capital assistance, business training, and strengthening the traditional market system